2022
DOI: 10.25259/sni_1201_2021
|View full text |Cite
|
Sign up to set email alerts
|

Spinal tuberculosis: A case series and a literature review

Abstract: Background: Spinal tuberculosis (TB) is a common form of extrapulmonary TB. Although the first line of the treatment is anti-TB medications, patients with severe neurological deficits, spinal instability, and/or kyphotic deformity often warrant surgery. Here, we report five cases of spinal TB requiring operative intervention at Hasan Sadikin General Hospital, Bandung, Indonesia. Case Description: We operated on five patients with spinal TB cases from 2019 to October 2021. In addition to appropriate medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The primary clinical manifestations in patients with recurrent thoracolumbar tuberculosis include pain, sinus tract formation, and neurological de cits, whereas patients with primary tuberculosis predominantly present with pain, night sweats, and low-grade fever. Notably, only 55.1% of recurrent patients experience pain, a signi cantly lower rate than the 83-100% observed in primary patients [15][16][17][18][19][20] Additionally, the frequency of low-grade fever and night sweats is relatively lower in recurrent patients, which may be associated with the continuation of anti-tuberculosis medication during the recurrent phase for some patients. Particularly striking is the observation that 44.9% of recurrent patients in this study did not exhibit pain upon recurrence and also presented with fewer tuberculous toxic symptoms such as low-grade fever and night sweats.…”
Section: Discussionmentioning
confidence: 99%
“…The primary clinical manifestations in patients with recurrent thoracolumbar tuberculosis include pain, sinus tract formation, and neurological de cits, whereas patients with primary tuberculosis predominantly present with pain, night sweats, and low-grade fever. Notably, only 55.1% of recurrent patients experience pain, a signi cantly lower rate than the 83-100% observed in primary patients [15][16][17][18][19][20] Additionally, the frequency of low-grade fever and night sweats is relatively lower in recurrent patients, which may be associated with the continuation of anti-tuberculosis medication during the recurrent phase for some patients. Particularly striking is the observation that 44.9% of recurrent patients in this study did not exhibit pain upon recurrence and also presented with fewer tuberculous toxic symptoms such as low-grade fever and night sweats.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no global or national epidemiological studies on spinal tuberculosis. However, it was found that spinal tuberculosis accounted for 69.11% of osteoarticular tuberculosis [ 6 , 21 ], and elderly patients over 60 years accounted for 44.08%. 24.30% of the patients were 20–39 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal tuberculosis is the most common and dangerous, and pathological fractures of tuberculosis may cause kyphosis. In recent years, with the increase in HIV infections and drug-resistant strains of TB, spinal tuberculosis has been increasing yearly [4][5][6]. For surgical methods, there are simple anterior approach, simple posterior approach, and anterior and posterior approach combined with debridement and bone graft fusion.…”
Section: Introductionmentioning
confidence: 99%